Cross-taxon congruence in wetlands: Assessing the value of waterbirds as surrogates of macroinvertebrate biodiversity in Mediterranean Ramsar sites. (February 2015) - Guareschi, S.; Abellán, P.; Laini, A.; Green, A.J.; Sánchez-Zapata, J.A.; Velasco, J.; Millán, A.
Highlights: Weak concordance between the community composition of waterbirds and macroinvertebrates. Negligible or negative correlations between metrics of their taxonomic richness. Results explained by contrasting responses to environmental gradients. Waterbirds can be poor indicators of aquatic biodiversity. Abstract: Wetlands are among the most threatened habitats and the species they support among the most endangered taxa. Measuring and monitoring wetland biodiversity is vital for conservation, restoration and management, and often relies on the use of surrogate taxa. Waterbirds are commonly used as flagships of biodiversity and are the subject of major conservation initiatives. Therefore, it is important to assess the extent to which waterbirds indicate the general biodiversity of wetlands and serve as surrogates. We explore the relationships between community composition and species richness of waterbirds and aquatic macroinvertebrates in 36 Ramsar wetlands in southern Spain to assess if waterbirds are good surrogates for other taxonomic groups. Specifically, we aimed to (i) test the congruence of patterns of species composition and richness among waterbirds and aquatic macroinvertebrates; and (ii) investigate which environmental variables are associated with the biodiversity patterns of waterbirds and macroinvertebrates, with the purpose of identifying key factors explaining potential discordance in these patterns. We found a limited concordance between assemblage patterns of both taxonomic groups that may be related to their contrasting responses to environmental gradients. Assemblages of waterbirds appear to be more affected by climate variables and water surface area, whereas conductivity was the most important factor influencing macroinvertebrate communities. Furthermore, we found a negligible or inverse relationship in their patterns of richness, with wetlands with higher waterbird species richness showing significantly lower richness of Hemiptera and macroinvertebrate families, and no significant relationship with Coleoptera. In addition, GLM models showed that, in general, different environmental variables are related with the richness patterns of the different taxonomic groups. Given the importance of the Ramsar convention for the conservation of an international network of wetlands, our findings underline the limited potential of waterbirds as aquatic biodiversity indicators in Mediterranean wetlands, and the need for caution when using waterbirds as flagships. An integrative analysis of different biological communities, using datasets from different taxonomic groups, is a necessary precursor for successful conservation policies and monitoring. Our results illustrate the need to create a diversified and complete network of protected sites able to conserve multiple components of wetland biodiversity.